Bioconsumption of phenols from effluents - Mishra M.K. (My University, 2025)
The bioconsumption of phenol and p-methylphenol from effluents by mixed culture have been investigated. The effect of pH, temperature and phenol concentrations on bioconsumption have been studied. It was observed that pH 7.0 and temperature 37°C favours a greater bioconsumption of phenol and p-methylphenol. An increase in initial phenol concentration in the medium increases the time required for the phenol bioconsumption.; The bioconsumption of phenol and p-methylphenol from effluents by mixed culture have been investigated. The effect of pH, temperature and phenol concentrations on bioconsumption have been studied. It was observed that pH 7.0 and temperature 37 °C favours a greater bioconsumption of phenol and p-methylphenol. An increase in initial phenol concentration in the medium increases the time required for the phenol bioconsumption.